Persistence of Initial Misanalysis With No Referential Ambiguity. (17th July 2015) - Nakamura, Chie; Arai, Manabu
Abstract: Previous research reported that in processing structurally ambiguous sentences comprehenders often preserve an initial incorrect analysis even after adopting a correct analysis following structural disambiguation. One criticism is that the sentences tested in previous studies involved referential ambiguity and allowed comprehenders to make inferences about the initial interpretation using pragmatic information, suggesting the possibility that the initial analysis persisted due to comprehenders' pragmatic inference but not to their failure to perform complete reanalysis of the initial misanalysis. Our study investigated this by testing locally ambiguous relative clause sentences in Japanese, in which the initial misinterpretation contradicts the correct interpretation. Our study using a self‐paced reading technique demonstrated evidence for the persistence of the initial analysis with this structure. The results from an eye‐tracking study further suggested that the phenomenon directly reflected the amount of support given to the initial incorrect analysis prior to disambiguating information: The more supported the incorrect main clause analysis was, the more likely comprehenders were to preserve the analysis even after the analysis was falsified. Our results thus demonstrated that the preservation of the initial analysis occurs not due to referential ambiguities but to comprehenders' difficulty to fully revise the highly supported initial interpretation.